The images of Donald Trump on online news media in Indonesia through photojournalism: media construction and readers’ perception - al Makmun, Muhammad Taufiq; Diah Kristina,; Kusciati, Karunia Purna; Fenty Kusumastuti, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to find out the representation of the President of the United States of America, Donald Trump, through photojournalism which is used to support the news coverage of the president in the Indonesian online news media. It is reader-response research examining photography representation in the Indonesian online news media: okezone.com, tribunnews.com, and detik.com in 2017-2020 to view the media construction and readers’ perception. The respondents consisted of the students of English Department, Universitas Sebelas Maret, Indonesia were chosen to represent the digital native online news readers in Indonesia. In order to get the readers’ perception, they were asked to “read” 15 photos of President Trump, 12 of them were taken from news coverages of three online news media: okezonecom, tribunnews.com, and detik.com; whereas the other three photos were taken from the White House official website. The finding shows that Donald Trump tends to be portrayed differently with those used by the White House official website. Furthermore, readers are able to recognize the official presidential photos among the photojournalism. Despite their awareness of the photo selections by the media, each photojournalism used in the survey is perceived both negatively and positively by the readers.